The effect of Cyclamen coum extract on pyocyanin production by Pseudomonas aeruginosa - Zahra Ahmadbeigi; Azra Saboora; Ahya Abdi-Ali (International Journal of Phytomedicine, 2014)
Researches have shown that some plants possess antimicrobial activity and the ability to overcome drug-resistant pathogens. Their frequent used in treatment of microbial infections has been led to isolation of the active compounds and evaluation of their antimicrobial properties. Cyclamen coum Miller is one of these plants with a secondary metabolite called saponin which has antimicrobial activity. Pyocyanin is one of the virulence factors in Pseudomonas aeruginosa, an opportunistic pathogen, causing lung diseases. The present study indicates the effect of cyclamen saponin extracts on pyocyanin production by P. aeruginosa. We prepared three different types of plant extracts (ethanolic, aqueous and butanolic) from tuber of C. coum. The effect of 0, 10 and 20 mg of cyclamen saponin were tested by agar disk diffusion technique. Pyocyanin purification was done from microbial broth culture and the extracted pyocyanin was measured by spectrophotometric method. Results showed that the production of pyocyanin was remarkably reduced by ethanolic extract of saponin. In addition increased saponin concentration led to further decrease in pyocyanin content.